Development of a large animal rabbit model for chronic periprosthetic joint infection - Yagi, Haruyo (Bone Joint Res, 2021)
AIMS: Periprosthetic joint infections (PJIs) and osteomyelitis are clinical challenges that are difficult to eradicate. Well-characterized large animal models necessary for testing and validating new treatment strategies for these conditions are lacking. The purpose of this study was to develop a rabbit model of chronic PJI in the distal femur. METHODS: Fresh suspensions of Staphylococcus aureus (ATCC 25923) were prepared in phosphate-buffered saline (PBS) (1 × 10(9) colony-forming units (CFUs)/ml). Periprosthetic osteomyelitis in female New Zealand white rabbits was induced by intraosseous injection of planktonic bacterial suspension into a predrilled bone tunnel prior to implant screw placement, examined at five and 28 days (n = 5/group) after surgery, and compared to a control aseptic screw group. Radiographs were obtained weekly, and blood was collected to measure ESR, CRP, and white blood cell (WBC) counts. Bone samples and implanted screws were harvested on day 28, and processed for histological analysis and viability assay of bacteria, respectively. RESULTS: Intraosseous periprosthetic introduction of planktonic bacteria induced an acute rise in ESR and CRP that subsided by day 14, and resulted in radiologically evident periprosthetic osteolysis by day 28 accompanied by elevated WBC counts and histological evidence of bacteria in the bone tunnels after screw removal. The aseptic screw group induced no increase in ESR, and no lysis developed around the implants. Bacterial viability was confirmed by implant sonication fluid culture. CONCLUSION: Intraosseous periprosthetic introduction of planktonic bacteria reliably induces survivable chronic PJI in rabbits. Cite this article: Bone Joint Res 2021;10(3):156–165.